Confessional Cultures and European Identity: Religion, Ideology, and Economics - Nelsen, Brent F. (Religions, 2023)
Proponents of greater European political unity through the development of the European Union (EU) have long sought to foster a “European” identity among citizens as a way of advancing their cause. And there is now a substantial body of scholarship devoted to understanding the social, economic, and demographic factors contributing to the development of such an identity. Recently, there has been a growing interest in cultural influences, but the possible impact of religion has been largely ignored. Using Eurobarometer 65.2 (2006), we show that religious groups differ systematically in their propensity to take “European” identity markers. Using multivariate analysis, we demonstrate that Catholics are most likely to be cognitive “Europeans”, while Protestants and other Christians are less likely to take such perspectives. Religiosity tends to reinforce the dominant propensity of each tradition. These religious differences persist even under statistical controls for other demonstrated influences, although their effects are strongest in the old Western European “core” of the EU. The long-term decline of Catholic religiosity thus has important implications for the future of “European” identities: their growth will depend increasingly on less “diffuse” and more variable influences, such as successful economic management by EU and national governments.